Chemistry of CS2- and SCNPh-adducts of the pyramidal phosphinidene-bridged complex [Mo2Cp(μ–κ1:κ1, η5-PC5H4)(CO)2(η6-HMes*)(PMe3)]. Issue 11 (27th February 2017) - Albuerne, Isabel G.; Alvarez, M. Angeles; García, M. Esther; García-Vivó, Daniel; Ruiz, Miguel A.
Abstract : Heterocumulene insertion into the metallocene Mo–P bond of the title complex enables further addition of different electrophiles at the P, S or N sites. Abstract : The title complex reacted readily with CS2 and SCNPh to give the phosphinidene–cumulene adducts [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -P(CS2 )C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] and [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -P(C(NPh)S)C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] respectively (Mes* = 2, 4, 6-C6 H2 t Bu3 ), as a result of the formal insertion of the CS bond of the heterocumulene into the metallocene Mo–P bond of the phosphinidene complex. The newly formed species bear a pyramidal P atom with a lone electron pair involved in fast inversion, and displayed strong nucleophilicity which enabled easy addition at the P site of carbon-based electrophiles and chalcogen atoms, while the uncoordinated S and N atoms were also competitive nucleophilic sites in these complexes. These air-sensitive materials readily added an O2 molecule in the solid state, to give the corresponding derivatives [Mo2 Cp{μ–κ 1 O :κ 1 S, η 5 -OP(O)(C(X)S)C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] (X = S, NPh), and the CS2 adduct reacted selectively with S8 in solution to give the sulfide derivative [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -P(S)(CS2 )C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )], which was stabilized through methylation, thus yielding the cationic complex [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -P(S)(C(SMe)S)C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] + . The CS2 adduct could be methylated selectively at either the P or CS sites, depending on the reagent used, to give respectively the cationic complexes [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -PMe(CS2 )C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] + or [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -P(C(SMe)S)C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] + . Further methylation could be accomplished through reaction with [Me3 O]BF4 to give the dipositive cation [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -PMe(C(SMe)S)C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] 2+ . In contrast, the SCNPh adduct was only methylated at the P site to yield the phosphanylthioformamidato complex [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -PMe(C(NPh)S)C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] +, but was readily protonated at the N site upon reaction with (NH4 )PF6, to give the phosphanylthioformamide-like derivative [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -P(C(NHPh)S)C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] + . In the presence of Na(BAr′4 ), this adduct was even able to displace chloride from the solvent (dichloromethane) to give the corresponding chloromethyl derivative [Mo2 Cp{μ–κ 1 P :κ 1 S, η 5 -P(CH2 Cl)(C(NPh)S)C5 H4 }(CO)2 (η 6 -HMes*)(PMe3 )] + . The structures of the new complexes were analyzed using spectroscopic, diffractometric and, in some cases, density functional theory methods.